Solving the human sustainability problem in short-termist societies - Graeme Maxton (The White Horse Press, 2021)
Society has so far failed to create a sustainable economic system because all conventional attempts to change the current paradigm lead to a short-term decline in the rate economic growth, resulting in higher inequality and unemployment, outcomes which are politically unacceptable. This article shows how to overcome this hurdle, by adopting 13 unconventional policies which reduce unemployment and inequality while cutting greenhouse-gas emissions, regardless of what happens to economic growth, and so allow for a gradual transition to a sustainable system in short-termist societies.